Modelling relationship among community participation, community-based tourism and sustainable tourism development of Krabi province, Thailand - Naranon, Phatnista
The tourism industry is one of the largest and fastest growing industries in the world and has increasingly become an important source of income, employment and wealth in many countries. In Krabi province of Thailand, tourist arrivals have been increasing and bring about an increasing number of hotels that have boosted the tourism receipts. However, the increase has come with its negative impact on sustainable tourism development. This study was conducted to ascertain factors that could improve sustainable tourism development. The main aim of the study is to ascertain the impacts of community participation and community-based tourism on sustainable tourism development in Krabi Province, Thailand. Specific objectives of the study, firstly, to determine the effect of community participation on sustainable tourism development. The second objective was to determine the effect of community participation on community-based tourism. The third objective was to determine the effect of community-based tourism on sustainable tourism development. The final objective was to examine the mediating effect of community-based tourism on the relationship between community participation and sustainable tourism development. This study adopted a cross-sectional research design. A total respondent of 286 hotel general managers were selected using simple random sampling from two districts namely: Mueang Krabi and Ko Lanta in Krabi Province, Thailand. A survey was conducted using self-administered questionnaires. Exploratory Factor Analysis was performed using Statistical Package for Social Science Program (SPSS) software version 21. Confirmatory Factor Analysis was conducted to assess the unidimensionality, validity and reliability of the theoretical constructs. Structural Equation Model (SEM) using the Analysis of Moment Structures (AMOS) software version 21 was applied to the dataset to test the proposed hypotheses. The finding of the study shows that community participation doe not have a significant effect on sustainable tourism development. However, community participation has a significant positive impact on community-based tourism. While, community-based tourism shows a significant positive impact on sustainable tourism development. The findings also significantly revealed that community-based tourism fully mediates the relationship between community participation and sustainable tourism development. The findings of the study contributed to the theoretical implication which proposed a new structural model that examined the relationships among community participation, community-based tourism and sustainable tourism development. In addition, the findings also suggested practical contributions to the local community, hotel general managers and Ministry of Tourism and Sports, Thailand on aspects to improve sustainable tourism development in Krabi. Future research should study community participation further by comparing between hotel general managers and tour operators as both are important towards community-based tourism and sustainable tourism development in Krabi Province, Thailand.